2022
DOI: 10.1111/gcb.16166
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sea ice and range expansion of sperm whales in the eclipse sound region of Baffin Bay, Canada

Abstract: Sperm whales (Physeter macrocephalus) are a cosmopolitan species but are only found in ice‐free regions of the ocean. It is unknown how their distribution might change in regions undergoing rapid loss of sea ice and ocean warming like Baffin Bay in the eastern Canadian Arctic. In 2014 and 2018, sperm whales were sighted near Eclipse Sound, Baffin Bay: the first recorded uses of this region by sperm whales. In this study, we investigate the spatiotemporal distribution of sperm whales near Eclipse Sound using vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…We further expect this species to be less sensitive to climatic change than other whales with more restrictive habitat preferences. To our knowledge, evidence of sperm whale range shifts related to climatic change is limited to examples where a pod expanded into new habitats made accessible by sea ice melting (Posdaljian et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further expect this species to be less sensitive to climatic change than other whales with more restrictive habitat preferences. To our knowledge, evidence of sperm whale range shifts related to climatic change is limited to examples where a pod expanded into new habitats made accessible by sea ice melting (Posdaljian et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, such avoidance behavior has never been documented in marine mammals at the scales we considered (i.e., >200 nm). As a highly migratory species adaptable to new habitats (Posdaljian et al., 2022), this is an intriguing possibility for sperm whales, with implications for recolonization potential.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of sea ice negatively affects organisms that rely on ice (e.g. emperor penguins and polar bears; Boonstra et al, 2020; Chown et al, 2022; Jenouvrier et al, 2020, 2021; Stirling & Derocher, 2012; Wege et al, 2021) but can lead to range expansion for other species (Chan et al, 2019; Chown et al, 2022; Christiansen et al, 2014; Feng et al, 2018; Posdaljian et al, 2022). Novel feeding interactions can then develop, which amplify the impact of species redistribution (Pecuchet et al, 2020).…”
Section: Biological Change At the Polesmentioning
confidence: 99%
“…Even though sperm whales are known to be seasonally resident in the Arctic, their geographic distribution at a finer scale and the timing of their arrivals and departures from the north are not well documented 5 . Sea ice is known to limit their distribution; sperm whales typically avoid sea ice covered areas 6 , 7 . In the North Pacific, sperm whales are found in Alaskan waters 8 , 9 , in the Bering Sea, the Bering Strait and the southern Chukchi Sea, up to latitudes of about 68° N 7 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in the North Atlantic, the sperm whales’ range extends much further north. Studies have reported sperm whales at latitudes of 75° N in Baffin Bay in the Northwest Atlantic 6 , 11 , 12 . In the Northeast Atlantic, the sperm whale’s range extends north to the Svalbard Archipelago, with observations as far as 81° N 13 17 .…”
Section: Introductionmentioning
confidence: 99%